Factors influencing MICE destination revisit intentions: A literature review - Ramadan, Ammar; Kasim, Azilah (Turyzm/Tourism, 2022)
The relationship between push and pull factors with the intention to revisit a destination has often been investigated in the context of general tourism. Not much is known on the factors influencing MICE destination revisit intentions, despite the numerous socioeconomic benefits that many countries have received from the MICE tourism business. This article attempts to fill the gap of knowledge by critically reviewing the literature using the integrative review approach. By reviewing, critiquing and synthesizing major literature on the issue, two push factors i.e. networking and educational opportunities and four pull factors i.e. destination image, travel costs, attraction and accessibility are established as influencing revisit intentions to MICE destination. Then a theoretical model of relationship between those factors and MICE destination revisit intentions is proposed.